PREPARATION OF SUSPENSION AND XP SULF PREPARATION IN ONE SOLUTION - Khakimov Poziljon Ahmadovich , Muzaffarov Adil Ahmadbekovich , Shadmanov Komoliddin Kazakdjanovich , Abdukadirov Hasanbek Dilshadbekovich (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article discusses the conditions of the Republic (hot climate, its geographical location and soil conditions) are very favorable for the reproduction of pests, so the pests find abundant food and a comfortable place in the fields, which in turn leads to further damage to crops, preventing large losses from pests, a new drug used.